Villagers’ Satisfaction Indicators on Village Information System in The Front Region - syofian; Tua F S, Harapan (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
This research aims at describing the process of services implementation through village information system based web and the villagers’ satisfaction from the aspects of satisfaction standardization. The method of the research was qualitative with hermeneutic phenomenology approach. It would see the texts of villagers’ life and experiences in using Village Information System Services. The data were analyzed by using the van kaam model. It was found that service satisfaction of the village information system in the context of individual experience identified from the staffs’ attitude, information, delivery, internal manager’s role, and time service accuracy. Based on the finding, it is recommended for further researcher to conduct a study about service implementation as well as e-government. The weakness of this research is that the researcher conducted it in a short time asking the individual’s experiences about the village service information system implementation.